Pemanfaatan Era Digital Dalam Memilih Jurusan Kuliah Yang Ideal - Zulkarnain; Lilis Indrayani; Sabinus Rainer N. Christi; Samuel Mathias Dauth Menai (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to socialize the importance of choosing a college major, as well as being able to make better use of technology in determining the ideal choice of major. This activity was carried out at SMK Negeri 2 Manokwari, which was attended by class XII students located in Manokwari Regency. This activity was carried out well followed by the students' responses so that discussion occurred. The results of the activity are students' knowledge about the importance of continuing their studies at university, it is important to choose a major that is in line with technological developments.